2021
DOI: 10.1186/s12886-021-02212-x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of etiology on surgical outcomes in neovascular glaucoma

Abstract: Background The authors sought to evaluate visual outcomes in patients with varying etiologies of neovascular glaucoma (NVG), who were treated with glaucoma drainage devices (GDD). Methods This was a retrospective case series of patients at a large academic teaching institution who had surgical intervention for neovascular glaucoma between September 2011 and May 2019. Eyes were included if there was documented neovascularization of the iris/angle wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 36 publications
0
15
0
2
Order By: Relevance
“…Another clinical characteristic that we report in this study, which is not commonly reported, is the level of glycosylated hemoglobin, which we found in our patients, a median of 8.37% (7.18 -9.70), which reflects poor systemic control. This is reflected in the causes of neovascular glaucoma since while in the literature the three most frequent causes (diabetic retinopathy, central retinal vein occlusion, and ischemic eye syndrome) are reported in percentages that vary between 33% (23)to 61.7% (24), our results show that in 92% of cases the most common cause in the Mexican population is diabetic retinopathy. With these data, we can infer that the Mexican population presents in more advanced stages of the disease, with worse metabolic and systemic control.…”
Section: Discussionmentioning
confidence: 52%
“…Another clinical characteristic that we report in this study, which is not commonly reported, is the level of glycosylated hemoglobin, which we found in our patients, a median of 8.37% (7.18 -9.70), which reflects poor systemic control. This is reflected in the causes of neovascular glaucoma since while in the literature the three most frequent causes (diabetic retinopathy, central retinal vein occlusion, and ischemic eye syndrome) are reported in percentages that vary between 33% (23)to 61.7% (24), our results show that in 92% of cases the most common cause in the Mexican population is diabetic retinopathy. With these data, we can infer that the Mexican population presents in more advanced stages of the disease, with worse metabolic and systemic control.…”
Section: Discussionmentioning
confidence: 52%
“…BCVA values were converted to a logarithm of minimum resolution angle (LogMAR) system for statistical analysis. Non-Snellen visual acuities were converted to finger counting (2.0), hand gestures (2.3), light perception (2.6), and no light perception (3.0) (8). The numbers of patients presenting before and after lockdown were evaluated in terms of age, gender, the eye(s) involved, etiology, IOP, BCVA, the medical or surgical treatment applied, and lens status.…”
Section: Methodsmentioning
confidence: 99%
“…The etiology of NVG also affects prognosis. For instance, an underlying retinal vein occlusion has been shown to have a worse visual prognosis after tube shunt surgery compared with other causes of neovascularization 104 . Unfortunately, it is not common for NVG eyes to progress to total blindness and discomfort despite medical and surgical therapy.…”
Section: Prognosismentioning
confidence: 99%
“…For instance, an underlying retinal vein occlusion has been shown to have a worse visual prognosis after tube shunt surgery compared with other causes of neovascularization. 104 Unfortunately, it is not common for NVG eyes to progress to total blindness and discomfort despite medical and surgical therapy. In cases of profound vision loss particularly associated with pain in eyes that are unlikely to benefit from other intervention, retrobulbar injection of alcohol or enucleation may be recommended to increase patient comfort.…”
Section: Prognosismentioning
confidence: 99%